RESPONS PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS KEDELAI (Glycine Max L. (MERILL)) DENGAN PEMBERIAN PUPUK ORGANIK CAIR - Dyah Karunia Sari; Yaya Hasanah; Toga Simanungkalit (Universitas Sumatera Utara, 2014)
Reseacrh on tittle respons of soybean (Glycine max L. (Merill)) varieties growth and productionwith application of liquid organic fertilizer aimed to evaluate the effect of three levels liquid organicfertilizer on four of soybean verieties growth and production in dry land. The experiment designwas factorial randomized block design with two factors and three replication. The first factor wasvarieties which consisted of Anjasmoro, Wilis, Detam 1, and Detam 2. The second factor was liquidorganic fertilizer with three levels: 0; 20; 40 cc/applications which applied for seven times at 2–8week after planting (WAP). The parameters was plant height, shoor root ratio, number ofproductive branches, seed dry weight per plot, and 100 seed dry weight. The result showed thateach variety had different growth and production. Liquid organic fertilizer increased plant height4-5 WAP, shoot root ratio, and seed dry weight per plot compared without application of liquidorganic fertilizer. Interaction between varieties and liquid organic fertilizer significantly affectednumber of productive branches and 100 seed dry weight. Wilis showed the best respons withapplication of 16.75 cc liquid organic fertilizer because of its ability to produce the higher 100 seeddry weight.Keywords : soybean, production, liquid organic fertilizer, variety